Stability analysis of safflower (Carthamus tinctorius L.) genotypes: Stability analysis of safflower (Carthamus tinctorius L.) genotypes - A H RATHOD; S B GHUGE; D K ZATE; A S MALVE (Journal of Oilseeds Research, 2023)
Among the twelve genotypes of safflower studied analysis of variance revealed significant genotypic differences among all the genotypes for thirteen morphological characters. The genotype PBNS-207 was the highest yielding, followed by PBNS-185 and PBNS-154. Environmental indices indicated that environment E4 (Somnathpur), E2 (Latur), E1 (Parbhani), and E3 were the most favourable (Badnapur). The stability parameters showed that PBNS-185 had the highest seed yield/plant stability.